Electrical impedance tomography in anaesthetised chickens (Gallus domesticus) - Wong, Adrian M.; Lum, Hei Y.; Musk, Gabrielle C.; Hyndman, Timothy H.; Waldmann, Andreas D.; Monks, Deborah J.; Bowden, Ross S.; Mosing, Martina (Frontiers in Veterinary Science, 2024)
The applicability of electrical impedance tomography (EIT) in birds is unknown. This study aimed to evaluate the use of EIT in anaesthetised chickens in four recumbency positions.Four adult Hyline chickens were anaesthetised with isoflurane in oxygen, and intubated endotracheally for computed tomography (CT). A rubber belt was placed around the coelom caudal to the shoulder joint. A chicken-specific finite element (FE) model, which is essential to generate anatomically accurate functional EIT images for analysis, was constructed based on the CT images obtained at the belt level. Ten additional chickens were anaesthetised with the same protocol. An EIT electrode belt was placed at the same location. The chickens were breathing spontaneously and positioned in dorsal, ventral, right and left lateral recumbency in a randomised order. For each recumbency, raw EIT data were collected over 2 minutes after 13 minutes of stabilisation. The data were reconstructed into functional EIT images. EIT variables including tidal impedance variation (TIV), centre of ventilation right to left (CoVRL) and ventral to dorsal (CoVVD), right to left (RL) ratio, impedance change (∆Z) and eight regional impedance changes including the dorsal, centraldorsal, central-ventral and ventral regions of the right and left regions were analysed. Four breathing patterns (BrP) were observed and categorised based on the expiratory curve (EC). A linear mixed model was used to compare EIT variables between recumbencies. Fisher's exact test was used to compare the frequencies of breathing patterns for each recumbency.The ∆Z observed was synchronous to ventilation, and represented tidal volume of the cranial air sacs as confirmed by CT. Significant differences were found in CoVVD and regional impedance changes between dorsal and ventral recumbencies (P<0.05), and in CoVRL, RL ratio and regional impedance changes between right and left recumbencies (P<0.05), which suggested a tendency for the distribution of ventilation to shift towards non-dependent air sacs. No differences were found for TIV and respiratory rate between recumbencies. Recumbency had a significant effect on the frequencies of each of the four BrPs (P<0.001).EIT can monitor the magnitude and distribution of ventilation of the cranial air sac in different recumbencies in anaesthetised chickens.